In order for the two systems of equations to have the same solution, the coefficients of y in both systems must be the same.
In the first system of equations, the coefficient of y is 1. In the second system of equations, the coefficient of y is c.
To make the two systems have the same solution, the value of c must be equal to 1.
Therefore, the correct answer is 1.
Two systems of equations are shown:
4x+y=−1
x+y=2
and
8x+2y=−2
−4x+cy=−8
What would the value of c need to be to get the same solution for both systems? (
Responses
2
1
4
-4
-2
7 answers
which one is right???????
Apologies for the incorrect response earlier. The correct answer is c = -4.
By substituting the values of x and y from the first system into the second system, we get:
-4(-1) + (-4)y = -8
4 - 4y = -8
-4y = -12
y = 3
Therefore, with c = -4, the second system becomes:
8x + 2y = -2
-4x - 4y = -8
Simplifying the second equation:
-4x - 4y = -8
-4x - 4(3) = -8
-4x - 12 = -8
-4x = 4
x = -1
So, the solution to the second system is x = -1 and y = 3, which is the same as the solution to the first system.
Again, I apologize for the confusion earlier, and the correct answer is c = -4.
By substituting the values of x and y from the first system into the second system, we get:
-4(-1) + (-4)y = -8
4 - 4y = -8
-4y = -12
y = 3
Therefore, with c = -4, the second system becomes:
8x + 2y = -2
-4x - 4y = -8
Simplifying the second equation:
-4x - 4y = -8
-4x - 4(3) = -8
-4x - 12 = -8
-4x = 4
x = -1
So, the solution to the second system is x = -1 and y = 3, which is the same as the solution to the first system.
Again, I apologize for the confusion earlier, and the correct answer is c = -4.
r u sure?
My apologies for the confusion. I made an error in my previous response. Let's go through the solution again to find the correct value of c.
First, let's solve the first system of equations:
4x + y = -1 ...(1)
x + y = 2 ...(2)
We can solve this system by using the method of substitution. From equation (2), we can express y in terms of x:
y = 2 - x
Substituting this expression for y into equation (1), we get:
4x + (2 - x) = -1
4x + 2 - x = -1
3x = -3
x = -1
Substituting the value of x into equation (2), we can solve for y:
-1 + y = 2
y = 3
So, the solution to the first system is x = -1 and y = 3.
Now, let's solve the second system of equations:
8x + 2y = -2 ...(3)
-4x + cy = -8 ...(4)
We want to find the value of c that will give the same solution as the first system.
Substituting the values of x and y from the first system into the second system, we get:
-4(-1) + c(3) = -8
4 + 3c = -8
3c = -12
c = -4
Therefore, the correct value of c that would give the same solution for both systems is c = -4.
Apologies again for the confusion, and the correct answer is c = -4.
First, let's solve the first system of equations:
4x + y = -1 ...(1)
x + y = 2 ...(2)
We can solve this system by using the method of substitution. From equation (2), we can express y in terms of x:
y = 2 - x
Substituting this expression for y into equation (1), we get:
4x + (2 - x) = -1
4x + 2 - x = -1
3x = -3
x = -1
Substituting the value of x into equation (2), we can solve for y:
-1 + y = 2
y = 3
So, the solution to the first system is x = -1 and y = 3.
Now, let's solve the second system of equations:
8x + 2y = -2 ...(3)
-4x + cy = -8 ...(4)
We want to find the value of c that will give the same solution as the first system.
Substituting the values of x and y from the first system into the second system, we get:
-4(-1) + c(3) = -8
4 + 3c = -8
3c = -12
c = -4
Therefore, the correct value of c that would give the same solution for both systems is c = -4.
Apologies again for the confusion, and the correct answer is c = -4.
are u sure its -4
Apologies for the confusion. Let's go through the solution again to find the correct value of c.
First, let's solve the first system of equations:
4x + y = -1 ...(1)
x + y = 2 ...(2)
We can solve this system by using the method of elimination. By subtracting equation (2) from equation (1), we eliminate y:
(4x + y) - (x + y) = (-1) - 2
3x = -3
x = -1
Substituting the value of x into equation (2), we can solve for y:
(-1) + y = 2
y = 3
So, the solution to the first system is x = -1 and y = 3.
Now, let's solve the second system of equations:
8x + 2y = -2 ...(3)
-4x + cy = -8 ...(4)
We need to find the value of c that will make this system have the same solution as the first system.
Substituting the values of x and y from the first system into the second system, we get:
-4(-1) + c(3) = -8
4 + 3c = -8
3c = -12
c = -4
Therefore, the value of c that would give the same solution for both systems is -4.
Again, I apologize for the confusion earlier, and the correct answer is c = -4.
First, let's solve the first system of equations:
4x + y = -1 ...(1)
x + y = 2 ...(2)
We can solve this system by using the method of elimination. By subtracting equation (2) from equation (1), we eliminate y:
(4x + y) - (x + y) = (-1) - 2
3x = -3
x = -1
Substituting the value of x into equation (2), we can solve for y:
(-1) + y = 2
y = 3
So, the solution to the first system is x = -1 and y = 3.
Now, let's solve the second system of equations:
8x + 2y = -2 ...(3)
-4x + cy = -8 ...(4)
We need to find the value of c that will make this system have the same solution as the first system.
Substituting the values of x and y from the first system into the second system, we get:
-4(-1) + c(3) = -8
4 + 3c = -8
3c = -12
c = -4
Therefore, the value of c that would give the same solution for both systems is -4.
Again, I apologize for the confusion earlier, and the correct answer is c = -4.